What Really Matters to Change Recipients: Dimensions of Supervisors' Change Communication. (September 2017) - Helpap, Sevda; Schinnenburg, Heike
While the importance of supervisors' communication for the successful implementation of organisational change is often emphasised, evidence regarding the actual dimensions of change communication and the reaction of change recipients is scarce. As communication is highly context and culture specific, this study included participants from Germany and India. To meet these research aims, we conducted focus group discussions (FGD) with overall 50 graduate students with work experiences from Germany and India. We identified key dimensions of informative, empathic and participatory change communication that are of high importance for change recipients. The German and Indian participants had similar expectations regarding the informative and empathic dimensions of change communication. However, interestingly, their assessment of the actual participation differed substantially, with consequences for their emotional responses. The findings emphasise the crucial role of supervisors' communication for employees' emotions in times of change. Supervisors thereby need to consider the diverse dimensions of their communication and stimulate employees' expectations regarding information, empathy and participation with different communicative activities and approaches. This study provides important insights into organisational change communication by analysing its key dimensions, linking it to employees' emotions and considering the cultural context.